Influence of Brand Image and Brand Trust on Purchase Decision - Kurniawan, Dani; Agus Rahayu; Puspo Dewi Dirgantiri; Vanessa Gaffar (Dinasti Publisher, 2022)
Digital technology is continuously evolving, and NFT, as one of the blockchain breakthroughs, is receiving a lot of attention. The goal of purchasing NFT transactions on the Opensea marketplace is a fascinating topic. This article discusses the impact of brand image and brand trust on Opensea marketplace users' purchase decision, either partially or simultaneously. This article uses a quantitative research method. Non-probability sampling was used, with purposive sampling as the sample technique. Meanwhile, 133 people who have completed NFT transactions on the Opensea marketplace were polled. The findings of this study show that brand image and brand trust has a favorable and significant impact on NFT purchase decision in the Opensea marketplace.